A perspective on the role of language about pain - van Rysewyk, Simon (Frontiers in Pain Research, 2023)
This article contributes a perspective on pain motivated by the philosopher Ludwig Wittgenstein. According to Wittgenstein, the child learns from others that the occasions on which it manifests certain reactions—the reactions that human beings manifest when injured—make it appropriate to self-ascribe “pain”. When the child can signal correctly that she is in the requisite bodily state, then she has a conception of pain. Using the concept pain to symbolise an experience also makes it possible to tell other people what is going on and to solicit their help in managing the pain. In pain discourse, we can say “Sam can tell that Jason is with pain”, or “She could tell you that Jason is with pain if she wanted to”. These uses are linked to social milieu where rules are learnt for the application of concepts, such as the concept stoicism. In many rural communities, adults tell other adults about pain when it interrupts work or social activities. Otherwise, it is normative to “carry on”. The rural stoic who tells another about pain only if he wants to can complicate clinical pain management, which can undermine the patient's special authority. In contrast, convergence in pain definitions and judgements between the patient and health professional can protect the authority of the patient and improve the clinical interaction. Pain is not simply a quale that is privately perceived; it must be capable of being expressed. Thus, pain has a social role, which is learnt. The study of linguistic rules in pain discourse could help explain the learning and application of the concept pain.